Increased Generation of Fibrocytes in Thyroid-Associated Ophthalmopathy - Douglas, Raymond S. (The Endocrine Society, 2010)
Context: The pathogenic basis for Graves’ disease (GD) continues to elude our understanding. Specifically why activating antibodies are generated against self-antigens remains uncertain as does the identity of the antigen(s) that provokes orbital involvement in GD, a process known as thyroid-associated ophthalmopathy (TAO). Objective: The aim of the study was to determine whether CD34(+) fibrocytes are generated more frequently in GD, whether they infiltrate orbital connective tissues in TAO, and whether they express the thyrotropin receptor (TSHR). Design/Setting/Participants: Generation of fibrocytes from peripheral blood mononuclear cells was examined in samples from 70 patients with GD and 25 healthy control subjects. Fibrocytes were characterized by flow cytometry. Orbital tissues and fibroblast culture strains were examined for their presence. Main Outcome Measures: The frequency of CD34(+) fibrocyte generation from peripheral blood cells, characterization of their phenotype, cytokine production, and their presence in affected orbital tissues were analyzed. Results: CD34(+)CXCR4(+)Col I(+) fibrocytes expressing IGF-I receptor are far more frequently generated from cultured peripheral blood mononuclear cells of donors with GD compared with healthy subjects. They express TSHR at high levels and TSH induces fibrocytes to produce IL-6 and TNF-α. Numerous CD34(+) fibrocytes were detected in orbital tissues in TAO but were absent in healthy orbits. Tissue-infiltrating fibrocytes express TSHR in situ and comprise a subpopulation of TAO-derived orbital fibroblasts. Conclusions: Our findings suggest that fibrocytes may participate in the pathogenesis of TAO because they express relevant autoantigens such as IGF-I receptor and functional TSHR and differentially accumulate in orbital tissue in TAO.